Effects of biological insecticides NeemAzal T/S and Pyrethrum FS EC and their interaction with organic products in treatments of pea aphid Acyrthosiphon pisum (Harris) (Hemiptera: Aphididae) on Pisum sativum (L.) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
The efficacy and effects of two biological insecticides, NeemAzal T/S® and PyrethrumFS EC, applied individually and in combination with Polyversum (a biological growthregulator and fungicide) and Biofa (an organic foliar fertilizer), in controlling Acyrthosyphon pisum population density were studied. Nurelle D (a synthetic insecticide), applied alone and in combination with Flordimex 420 (a synthetic growth regulator), was used as a standard. The products were applied once (at budding stage) or twice (at budding and flowering stages). Twenty-four variants were studied. The interaction of Pyrethrum with Biofa was the most efficient variant of the biological products, causing a reduction in aphid density that reached 48.2% after double treatment, while Pyrethrum+Polyversum (42.5%) was the second most successful treatment. The combination of Pyrethrum with Biofa achieved the highest efficacy and synergism and their efficacy approached that of the synthetic insecticide.
Keywords: Forage pea; Acyrthosiphon; Biopesticides; Insecticides